Modified ternary positive electrode material and preparation method and application thereof
Through melt blending coating technology, the problem of uneven distribution of the surface coating elements of the positive electrode material of lithium-ion batteries is solved, uniform coating is achieved, battery performance is improved, and production costs and waste liquid generation are reduced.
Patent Information
- Application Number
- CN202411650118.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-14
AI Technical Summary
In the existing surface modification technology of the positive electrode material of lithium-ion batteries, the coating elements are unevenly distributed and complex in operation, high cost, and may produce harmful waste liquid.
Using melt blend coating technology, polymer material is melt-tightened and refined as a coating medium with ternary positive electrode material and coating agent in a mixer, and then calcined under an oxygen atmosphere to achieve uniform distribution of the coating layer.
The uniform distribution of the coating agent on the surface of the positive electrode material is achieved, the ionic conductivity is improved, the electrolyte is used to avoid the erosion of the positive electrode active substance, the production cost is reduced, and the generation of waste liquid is avoided.
Smart Images

Figure CN119447258A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a modified ternary positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have become an important energy storage method in mobile electronic devices, electric vehicles and energy storage systems due to their high energy density, long life and good charge and discharge cycle performance. The performance of lithium-ion batteries depends largely on the performance of the battery's positive electrode materials. At present, common lithium-ion battery positive electrode materials include lithium iron phosphate, lithium nickel cobalt manganese oxide (NCM for short), lithium nickel cobalt aluminum oxide (NCA for short), etc. These positive electrode materials are usually prepared by high-temperature solid-phase reactions, and in order to further improve their electrical properties, researchers have developed a variety of surface modification technologies, such as coating technology.
[0003] Existing surface coating technologies mainly include dry coating and liquid coating. Dry coating is to mechanically mix and calcine the ternary cathode material and the coating agent, while liquid coating is to disperse the ternary cathode material in a liquid medium and make the coating material adhere to the surface of the cathode material through chemical reaction.
[0004] Although the existing surface coating technology can improve the electrical properties of positive electrode materials to a certain extent, there are also some problems and limitations. For example, dry coating is achieved through physical mixing, so the distribution of the coating elements on the surface of the positive electrode material may be uneven, which will affect the electronic and ionic conductivity of the material, as well as the erosion of the positive electrode active material by the electrolyte. Although liquid phase coating can improve the uniformity of the distribution of the coating elements on the surface of the positive electrode material compared to dry coating, this method is complicated to operate, has high cost, and may produce harmful waste liquid during the coating process.
[0005] Therefore, how to achieve uniform distribution of coating elements on the surface of positive electrode materials while avoiding the generation of harmful waste liquid is an urgent problem to be solved in the current field of surface modification technology of positive electrode materials for lithium-ion batteries.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The object of the present invention is to provide a modified ternary positive electrode material and a preparation method and application thereof, so as to solve or improve the above-mentioned technical problems.
[0008] The present invention can be implemented like this:
[0009] In a first aspect, the present invention provides a method for preparing a modified ternary cathode material, comprising the following steps:
[0010] The polymer material is added as a coating medium into an internal mixer for melting, and then the ternary positive electrode material and the coating agent are added and mixed together to obtain a composite material; the composite material is calcined in an oxygen atmosphere to evaporate the polymer material to obtain a modified ternary positive electrode material.
[0011] In an optional embodiment, the mass of the ternary positive electrode material is 5wt% to 50wt% of the polymer material.
[0012] In an optional embodiment, the mass of the coating agent is 0.03wt% to 2wt% of the ternary positive electrode material.
[0013] In an optional embodiment, the polymer material includes at least one of polylactic acid, polypropylene, polyethylene and polyethylene glycol.
[0014] In an optional embodiment, the coating agent includes at least one of zirconium oxide, yttrium oxide, niobium oxide, aluminum oxide, titanium oxide, magnesium oxide, cobalt oxide, tungsten oxide, lithium cobaltate, aluminum fluoride and aluminum phosphate.
[0015] In an optional embodiment, the banburying time is not less than 1 hour, the melting point of the polymer material is ≤ the banburying temperature ≤ 250° C., and the banburying speed is 100 rpm to 200 rpm.
[0016] In an alternative embodiment, calcination is performed in an air atmosphere or an oxygen atmosphere.
[0017] In an optional embodiment, the calcination temperature is 300° C. to 800° C., and the calcination time is 5 h to 12 h.
[0018] In a second aspect, the present invention provides a modified ternary positive electrode material prepared by the preparation method of any one of the aforementioned embodiments.
[0019] In a third aspect, the present invention provides a battery, wherein the positive electrode material of the battery is the modified ternary positive electrode material of the aforementioned embodiment.
[0020] The beneficial effects of the present invention include:
[0021] By adding the polymer material as the coating medium into the internal mixer for melting, the molten polymer material has good fluidity, which can provide good flow and mixing conditions for the ternary positive electrode material and the coating agent, so that the coating agent and the ternary positive electrode material can be fully and evenly mixed. In addition, the above materials will be repeatedly sheared and extruded in the internal mixer, which can further improve the mixing uniformity of the coating agent and the ternary positive electrode material. After the internal mixing is completed, by calcining the composite material in an oxygen atmosphere, the polymer material can be basically volatilized completely, and a ternary positive electrode material with a uniform coating layer can be obtained.
[0022] The method is simple to operate and has low cost. It can achieve uniform coating of the coating agent on the surface of the ternary positive electrode material and avoid the generation of waste liquid. The obtained modified ternary positive electrode material has high ionic conductivity and can avoid the corrosion of the electrolyte on the positive electrode active material. The modified ternary positive electrode material is further prepared into a battery, which can make the battery have a high discharge specific capacity and good cycle performance, and a low internal resistance growth during the cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 This is a SEM image of the modified ternary cathode material provided in Example 1;
[0025] Figure 2 This is the SEM image of the modified ternary positive electrode material provided in Comparative Example 1. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0027] The modified ternary positive electrode material provided by the present invention and its preparation method and application are described in detail below.
[0028] The present invention provides a method for preparing a modified ternary positive electrode material, comprising the following steps:
[0029] The polymer material is added as a coating medium into an internal mixer for melting, and then the ternary positive electrode material and the coating agent are added and mixed together to obtain a composite material; the composite material is calcined in an oxygen atmosphere to evaporate the polymer material to obtain a modified ternary positive electrode material.
[0030] The polymer material is a carbon-containing substance that can be melted and volatilized under oxygen calcination conditions. In some typical embodiments, the polymer material may include at least one of polylactic acid, polypropylene, polyethylene and polyethylene glycol.
[0031] In the present invention, the molten polymer material has good fluidity, which can provide good flow and mixing conditions for the ternary positive electrode material and the coating agent, so that the coating agent and the ternary positive electrode material are fully and evenly mixed. In addition, the above materials are repeatedly sheared and extruded in the internal mixer, which can further improve the mixing uniformity of the coating agent and the ternary positive electrode material.
[0032] In some optional embodiments, the ternary positive electrode material may be a nickel-cobalt-manganese ternary positive electrode material, a nickel-cobalt-aluminum ternary positive electrode material and / or a sodium-electrolyte layered oxide positive electrode material.
[0033] In some optional embodiments, the mass of the ternary positive electrode material can be 5wt% to 50wt% of the polymer material, such as 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt% or 50wt%, etc., or it can be other values within the range of 5wt% to 50wt%.
[0034] If the mass of the ternary positive electrode material is too small, the processing amount each time will be small and the efficiency will be low; if the mass of the ternary positive electrode material is too large, it will affect the viscosity of the coating medium, resulting in poor coating uniformity of the subsequent coating agent, direct exposure of some new interfaces, and direct contact with the electrolyte during the cycle to produce side reactions, resulting in deterioration of the cycle performance and high temperature performance.
[0035] In some optional embodiments, the mass of the coating agent can be 0.03wt% to 2wt% of the ternary positive electrode material, such as 0.03wt%, 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt% or 2wt%, etc., or it can be other values within the range of 0.03wt% to 2wt%.
[0036] If the mass of the coating agent is too small, it is difficult to effectively and completely coat the surface of the ternary positive electrode material; if the mass of the coating agent is too large, it is easy to cause the coating uniformity to deteriorate.
[0037] As an example, the coating agent may include at least one of zirconium oxide, yttrium oxide, niobium oxide, aluminum oxide, titanium oxide, magnesium oxide, cobalt oxide, tungsten oxide, lithium cobaltate, aluminum fluoride and aluminum phosphate. In addition, other coating agents may also be used.
[0038] In some optional implementations, the banburying time is not less than 1 hour, such as 1 hour, 2 hours, 3 hours or 4 hours, etc. The banburying time can be adjusted according to actual conditions.
[0039] In some optional embodiments, the melting point of the polymer material is ≤ the banburying temperature ≤ 250°C. Controlling the banburying temperature within this range can ensure that the polymer material is always in a molten state during the banburying process, and can prevent the polymer material from volatilizing into carbon due to excessively high temperature.
[0040] In some optional embodiments, the rotating speed of the internal mixing may be 100 rpm to 200 rpm, such as 100 rpm, 150 rpm or 200 rpm, etc., or may be other values within the range of 100 rpm to 200 rpm.
[0041] After the internal kneading is completed, the mixture is cooled to obtain a composite material.
[0042] In the present invention, the calcination of the composite material is carried out in an air atmosphere or an oxygen atmosphere.
[0043] The calcination temperature can be 300°C to 800°C, such as 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, or other values within the range of 300°C to 800°C.
[0044] If the calcination temperature is higher than 800°C, the coating agent will easily be completely doped into the bulk of the positive electrode material, and the coating effect will not be achieved.
[0045] The calcination time can be 5 h to 12 h, such as 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h or 12 h, etc., or other values within the range of 5 h to 12 h.
[0046] Under the above calcination temperature and time, the polymer material can be basically volatilized completely, and the coating agent can form a uniform coating layer on the surface of the ternary positive electrode material.
[0047] As mentioned above, the preparation method of the modified ternary positive electrode material provided by the present invention is simple to operate and has low cost. It can not only achieve uniform coating of the coating agent on the surface of the ternary positive electrode material, but also avoid the generation of waste liquid.
[0048] Correspondingly, the present invention also provides a modified ternary positive electrode material prepared by the preparation method of any one of the aforementioned embodiments.
[0049] The modified ternary positive electrode material comprises a ternary positive electrode material and a coating layer coated on the surface of the ternary positive electrode material. The coating layer uniformly coats the surface of the ternary positive electrode material.
[0050] In addition, the modified ternary positive electrode material provided by the present invention also has relatively high ionic conductivity, and can prevent the electrolyte from corroding the positive electrode active material.
[0051] Furthermore, the present invention also provides a battery, the positive electrode material of the battery is the above-mentioned modified ternary positive electrode material.
[0052] The battery has a high discharge specific capacity and good cycle performance, and a low internal resistance increase during the cycle.
[0053] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0054] Example 1
[0055] This embodiment provides a modified ternary positive electrode material, and the preparation method thereof includes:
[0056] S1: 1 kg of polylactic acid was added into an internal mixer for melting;
[0057] S2: After the polylactic acid is melted, add NCM613 ternary positive electrode material, the mass of the ternary positive electrode material is 30wt% of the polylactic acid, and then add coating agent titanium oxide, the mass of titanium oxide is 0.3wt% of the ternary positive electrode material, and knead at 250°C and 150rpm for 1h, take out and cool to obtain a composite material.
[0058] S3: The composite material is calcined at 500° C. for 8 h in an air atmosphere to obtain a modified ternary positive electrode material.
[0059] The modified ternary positive electrode material comprises a NCM613 ternary positive electrode material and a titanium oxide coating layer uniformly coated on the surface of the NCM613 ternary positive electrode material.
[0060] Example 2
[0061] This embodiment provides a modified ternary positive electrode material, and the preparation method thereof includes:
[0062] S1: 1 kg of polylactic acid was added into an internal mixer for melting;
[0063] S2: After the polylactic acid is melted, add NCM613 ternary positive electrode material, the mass of the ternary positive electrode material is 5wt% of the polylactic acid, and then add coating agent titanium oxide, the mass of titanium oxide is 0.03wt% of the ternary positive electrode material, and knead at 200℃ and 200rpm for 1h, take out and cool to obtain a composite material.
[0064] S3: calcining the composite material at 300° C. for 12 h in an air atmosphere to obtain a modified ternary positive electrode material.
[0065] The modified ternary positive electrode material comprises a NCM613 ternary positive electrode material and a titanium oxide coating layer uniformly coated on the surface of the NCM613 ternary positive electrode material.
[0066] Example 3
[0067] This embodiment provides a modified ternary positive electrode material, and the preparation method thereof includes:
[0068] S1: 1 kg of polylactic acid was added into an internal mixer for melting;
[0069] S2: After the polylactic acid is melted, add NCM613 ternary positive electrode material, the mass of the ternary positive electrode material is 50wt% of the polylactic acid, and then add coating agent titanium oxide, the mass of titanium oxide is 0.5wt% of the ternary positive electrode material, and knead at 180℃ and 100rpm for 3h, take out and cool to obtain a composite material.
[0070] S3: The composite material is calcined at 800° C. for 5 h in an air atmosphere to obtain a modified ternary positive electrode material.
[0071] The modified ternary positive electrode material comprises a NCM613 ternary positive electrode material and a titanium oxide coating layer uniformly coated on the surface of the NCM613 ternary positive electrode material.
[0072] Example 4
[0073] The difference between this embodiment and embodiment 1 is that the polymer material is replaced by polypropylene.
[0074] Example 5
[0075] The difference between this embodiment and embodiment 1 is that the polymer material is replaced by polyethylene.
[0076] Example 6
[0077] The difference between this embodiment and embodiment 1 is that the polymer material is replaced by polyethylene glycol.
[0078] Example 7
[0079] The difference between this embodiment and embodiment 1 is that the coating agent is replaced by alumina.
[0080] Example 8
[0081] The difference between this embodiment and embodiment 1 is that the coating agent is replaced by lithium cobalt oxide.
[0082] Example 9
[0083] The difference between this embodiment and embodiment 1 is that the coating agent is replaced by aluminum fluoride.
[0084] Example 10
[0085] The difference between this embodiment and embodiment 1 is that the coating agent is replaced by aluminum phosphate.
[0086] Embodiment 11
[0087] The difference between this embodiment and embodiment 1 is that the ternary positive electrode material is replaced by NCM811.
[0088] Example 12
[0089] The difference between this embodiment and embodiment 1 is that the ternary positive electrode material is replaced with N90C0.9A0.1 ternary positive electrode material.
[0090] Comparative Example 1
[0091] This comparative example provides a modified ternary positive electrode material, and its preparation method includes:
[0092] 1 kg of NCM613 ternary positive electrode material was mixed with titanium oxide in an internal mixer for 1 hour. The mass of titanium oxide was 0.3 wt % of the ternary positive electrode material. After the mixing, the mixture was calcined at 500 ° C for 8 hours in an air atmosphere to obtain a modified ternary positive electrode material.
[0093] That is, this comparative example does not use polymer material as a coating medium during the preparation process.
[0094] Comparative Example 2
[0095] The difference between this comparative example and Example 1 is that S1 is not performed, and the unmelted polymer material, the ternary positive electrode material and the coating agent are directly kneaded together.
[0096] The remaining steps and conditions are the same as in Example 1.
[0097] Comparative Example 3
[0098] The difference between this comparative example and Example 1 is that the mass of the ternary positive electrode material is 2wt% of the polymer material.
[0099] Comparative Example 4
[0100] The difference between this comparative example and Example 1 is that the mass of the ternary positive electrode material is 55wt% of the polymer material.
[0101] Comparative Example 5
[0102] The difference between this comparative example and Example 1 is that the mass of the coating agent is 5wt% of the ternary positive electrode material.
[0103] Comparative Example 6
[0104] The difference between this comparative example and Example 1 is that the banburying temperature is 300°C.
[0105] Comparative Example 7
[0106] The difference between this comparative example and Example 1 is that the calcination is carried out under an inert atmosphere (nitrogen atmosphere).
[0107] Comparative Example 8
[0108] The difference between this comparative example and Example 1 is that the calcination temperature is 900°C.
[0109] Test example
[0110] ① The modified ternary cathode materials obtained in Example 1 and Comparative Example 1 were observed by scanning electron microscope. The results are as follows: Figure 1 and Figure 2 shown.
[0111] Depend on Figure 1 and Figure 2 It can be seen that: TiO2 is evenly attached to the surface of each positive electrode material in the embodiment, and there is basically no uncoated area. In the comparative example, it can be seen that although the surface of the positive electrode material is also coated with TiO2, the surface of some positive electrode materials is still relatively smooth and is not coated with TiO2.
[0112] ②. The modified ternary positive electrode materials obtained in the above Examples 1 to 12 and Comparative Examples 1 to 8 were subjected to residual alkali test, and the results are shown in Table 1.
[0113] The residual alkali test method is as follows: using pure water as the solvent, stir the positive electrode material in water for 30 minutes to dissolve the residual LiOH and Li2CO3 on the surface of the material in water. After filtering, use the potentiometric titration method to measure the alkali content in the water, which is the residual alkali on the surface of the positive electrode material.
[0114] Table 1 Test results
[0115]
[0116]
[0117] It can be seen from Table 1 that the alkali content of the ternary positive electrode material prepared by the method provided in the embodiment of the present invention is significantly lower than that of the comparative example. This is precisely because the uniformity of the coating allows the residual alkali on the surface to react.
[0118] ③. The modified ternary positive electrode materials obtained in the above Examples 1 to 12 and Comparative Examples 1 to 8 were respectively prepared into button batteries according to the following methods, and the performance of the button batteries was tested. The results are shown in Table 2.
[0119] The preparation method of button cell is as follows: the prepared cathode material finished product is mixed as active material with binder polyvinylidene fluoride (PVDF) and conductive agent acetylene black in a mass ratio of 90:5:5 and ground evenly, then a certain amount of nitrogen methyl pyrrolidone (NMP) is added as a dispersant to disperse the mixture, and then ground into a uniform slurry and coated on aluminum foil. The coated electrode material is dried in a vacuum oven at 110°C, and then the dried electrode material is rolled by a roller machine, and then dried in a vacuum oven at 120°C for 12h. The dried electrode material is punched, weighed, and the battery is assembled in a glove box. The electrolyte used for assembling the battery is an electrolyte composed of DMC+EC solvent containing 1MLiPF6, and the electrode sheet of the cathode material is used as the working electrode and the lithium sheet is used as the counter electrode. Button cell test conditions: 0.1C discharge specific capacity is tested in the charge and discharge voltage range of 2.8V to 4.4V at 25°C. The cycle performance test was carried out at 45°C, 2.8V to 4.4V voltage range and 1C / 1C rate.
[0120] Table 2 Test results
[0121]
[0122] It can be seen from Table 2 that the modified ternary positive electrode material prepared by the method provided in the embodiment of the present invention has a lower internal resistance and can enable the corresponding battery to have a higher discharge specific capacity and good cycle performance.
[0123] In summary, the method provided by the present invention has at least the following advantages:
[0124] (1) The problem of uneven distribution of coating elements on the surface of positive electrode materials in the existing dry coating technology is solved, which is beneficial to improve the electronic and ionic conductivity of the positive electrode material and reduce the erosion of the electrolyte on the positive electrode active material.
[0125] (2) It solves the problems of the existing liquid phase coating technology, which is complex to operate, high cost, and may produce harmful waste liquid during the coating process.
[0126] (3) A new type of melt blending coating technology is provided, which is simple to operate and does not produce harmful waste liquid.
[0127] (4) The coating elements are evenly distributed on the surface of the positive electrode material, which improves the coating effect and is beneficial to improving the electrical properties of the positive electrode material of the lithium-ion battery.
[0128] (5) It can be applied to different ternary cathode materials and coating agents.
[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a modified ternary positive electrode material, characterized in that: The following steps are involved: A polymer material is added as a coating medium into an internal mixer for melting, and then a ternary positive electrode material and a coating agent are added and mixed together to obtain a composite material; the composite material is calcined in an oxygen atmosphere to evaporate the polymer material to obtain a modified ternary positive electrode material.
2. The preparation method according to claim 1, characterized in that: The mass of the ternary positive electrode material is 5wt% to 50wt% of the polymer material.
3. The preparation method according to claim 2, characterized in that: The mass of the coating agent is 0.03wt% to 2wt% of the ternary positive electrode material.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The polymer material includes at least one of polylactic acid, polypropylene, polyethylene and polyethylene glycol.
5. The preparation method according to any one of claims 1 to 3, characterized in that: The coating agent includes at least one of zirconium oxide, yttrium oxide, niobium oxide, aluminum oxide, titanium oxide, magnesium oxide, cobalt oxide, tungsten oxide, lithium cobaltate, aluminum fluoride and aluminum phosphate.
6. The preparation method according to any one of claims 1 to 3, characterized in that: The banburying time is not less than 1 hour, the melting point of the polymer material is ≤ the banburying temperature ≤ 250° C., and the banburying speed is 100 rpm to 200 rpm.
7. The preparation method according to any one of claims 1 to 3, characterized in that: Calcination is carried out in an air atmosphere or an oxygen atmosphere.
8. The preparation method according to any one of claims 1 to 3, characterized in that: The calcination temperature is 300°C to 800°C, and the calcination time is 5h to 12h.
9. A modified ternary cathode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. A battery, characterized in that: The positive electrode material of the battery is the modified ternary positive electrode material as described in claim 9.